Objektif Syariah Dalam Pemberian Mahar - Hj Muh. Ali, Hasbi; Hj Azahari, Raihanah (Jurnal Fiqh, 2017)
Mahr is money or property which the wife is entitled to receive from the husband upon marriage. Islam not only has changed the system of mahr applied in the pre-Islamic time, but also has shown the importance and advantages of mahr in marriage institution. In Islam, mahr does not represent the price of a woman, but mahr is given as a form of recognition and dignity to the women who will be married to a man. However, mahr is still viewed as a payment to have a sexual relationship with a woman. This narrowed view not only lowers the status of women in marriage, but also gives negative understanding on the objective of mahr, as in pre-Islamic traditions it was seen as a gift to legalise sexual relationship. Therefore, this study was conducted to discuss the position of mahr in Islam, the objective of the mahr and the importance of mahr to women. Library research was the primary method of data collection, while deductive method was used in data analysis. This study shows that the objectives of mahr are to give property rights to women to represent the dignity of women and to provide socioeconomic protection to women.